Performance Analysis of Thermodynamic Indices and Atmospheric Stability Parameters in Thunderstorm Prediction: The Case of Samsun - Ahmet Can Kaya; Veli Yavuz (Doğal Afetler ve Çevre Dergisi)
In this study, the performance of thermodynamic indices and atmospheric stability parameters in thunderstorm prediction was analyzed for a five-year period between 2018 and 2022 using data from Samsun radiosonde station and aviation observations from Samsun Çarşamba Airport. The thermodynamic indices and atmospheric stability parameters used in the study are Showalter Index (SI), Lifted Index (LI), Severe Weather Threat Index (SWEAT), K-Index (KI), Totals Totals Index (TTI), Convective Available Potential Energy (CAPE), Convective Inhibition (CIN), and Bulk Richardson Number (BRN). Statistical performance tests such as Probability of Detection (POD), False Alarm Ratio (FAR), Miss Rate (MR), Critical Success Index (CIS), Hiedke Skill Score (HSS), and True Skill Score (TSS) were used to measure the success of the indices and parameters in predicting thunderstorm events. The analyses were performed using R and Excel. According to the results, the most successful index in thunderstorm prediction was SI, while the performance of CAPE and BRN parameters was the lowest. Based on all these analyses, it is observed that the majority of thunderstorms occur during the hottest months of the year and the hottest hours of the day. This indicates that most thunderstorms occur due to heating. In some events, the indices and parameters did not even reach the threshold value determined for thunderstorm formation. It is obvious that the prediction accuracy will be further improved if the thresholds of the indices and parameters are optimized for Samsun. Furthermore, evaluating multiple indices and parameters instead of relying on a single index or parameter for thunderstorm prediction will increase consistency and lead to more accurate results.